SUMOylation Regulates Neutrophil Phagocytosis and Migration - Ran Zhang; Wanying Miao; Jin Zhang; Xinyuan Yu; Lihong Dang; Ata Ur Rehman; Feng Xu; Huaxin Sheng; G. Chad Hughes; Joseph P. Mathew; Jörn Karhausen; Wei Yang (Pharmaceuticals)
Introduction: Accumulating evidence indicates that neutrophils undergo reprogramming of their effector functions as they migrate from the bloodstream into an inflamed tissue. Here, we examined the role of the small ubiquitin-like modifier (SUMO) conjugation in modulating neutrophil functional changes in the inflammatory microenvironment. Methods: Primary human and murine neutrophils were used to assess SUMOylation levels in vitro by Western blotting and results were validated in clinical samples from patients undergoing surgery involving hypothermic circulatory arrest. SUMOylation was inhibited with TAK-981, and its impact on neutrophil migration, NETosis, and phagocytosis was assessed in vitro. The in vivo effect of TAK-981 on neutrophil tissue infiltration was further evaluated using a sterile sponge assay in mice. Results: Our results demonstrated that neutrophil SUMOylation was induced by factors of the inflammatory microenvironment (temperature and oxidative stress) and inflammatory stimulants in vitro, and under conditions of general inflammatory activation in patients. Further, we found that blocking SUMOylation with TAK-981 in vitro blunted neutrophil migration and phagocytosis but did not affect NETosis. Notably, TAK-981 treatment reduced neutrophil accumulation in sterile sponges in mice. Conclusions: Our work identifies SUMOylation as a novel mechanism of neutrophil tissue reprogramming. Blocking SUMOylation may provide a therapeutic option to limit the contribution of neutrophils to inflammation-associated tissue damage.